An Analysis of Intra-Sentential Code Mixing in the YouTube Podcast Video by Timothy Ronald Featuring Agatha Chelsea - Ni Komang Anik Supadmi; Putu Gede Budiartha (Universitas Islam Negeri Palopo, 2025)
This study investigates the phenomenon of intra-sentential code mixing in the YouTube podcast video by Timothy Ronald featuring Agatha Chelsea, titled